“Bridge population”: sex workers or their clients? – STI prevalence and risk behaviors of clients of female sex workers in China - Huang, Z.J. (AIDS Care, 2011)
As the HIV/AIDS epidemic and the spread of sexually transmitted infections (STIs) in China has come to the forefront of public health attention, female sex workers (FSWs) and their clients (CFSWs) are becoming increasingly important to HIV/STI prevention efforts. This secondary analysis uses data abstracted from the Chinese Health and Family Life Survey 1999–2000 to report prevalence rates of two STIs as well as sexual risk behaviors for CFSWs – men who paid for sex with FSWs in the past 12 months – in comparison with men who had not patronized FSWs. Among 1879 Chinese CFSWs who completed anonymous interviews and urine testing, 152 (6.3%, weighted) said they had paid for sex in the past 12 months and 18.8% of CFSWs (weighted) tested positive for gonorrhea. CFSWs were 10 times more likely to have an STI (either self-reported or tested) than non-client Chinese men, and they were equally likely to use condoms inconsistently with their spouses. This study highlights the importance of studying CFSWs who use condoms inconsistently and do not practice safe sex with their spouse as a potential bridge population. Prevention and intervention efforts should target this bridge population and include education on HIV/AIDS and STI transmission, condom promotion, marriage counseling, destigmatization of HIV and STIs, and promotion of STI diagnosis and treatment.